PENGARUH MANAJEMEN LABA TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI TAHUN 2018-2020 - Janah, Arita Fitriatul; Wiryaningtyas, Dwi Perwitasari; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
A rational company will always try to maximize the profits it gets. The company will maximize profits to improve financial performance and firm value. The purpose of this study was to analyze and examine the effect of earnings management on firm value with financial performance as an intervening variable. This research is a quantitative research. The population in this study are mining companies listed on the Indonesia Stock Exchange in 2018-2020. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM).The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that earnings management has no significant effect on financial performance, earnings management has no proven effect on firm value, financial performance has a significant effect on firm value. The results of the indirect effect hypothesis test show that the earnings management variable has a positive but not significant effect.